A COMPARISON OF VALUE- AND TIME-WEIGHTED UNIT - Gerber, Eugene (My University, 2011)
Unit trust returns are published and quoted regularly in various media publications. These returns, calculated as Time-Weighted Rates of Return, do not reflect the actual returns that investors perceive. The timing of capital flows into and out of the funds affects the real returns that investors experience, and can be calculated using Value-Weighted Rates of Return, also referred to as Dollar-Weighted Rates of Return. This research report compared the Dollar- and Time-Weighted Rates of Return for 60 South African unit trusts from the second quarter of 1998 to the second quarter of 2005. The actual returns were compared to expected returns based on random capital flows, and to returns based on constant and inflation linked capital flows. If investors were creating superior returns by moving capital into and out of a unit trust during periods of positive and negative returns respectively, then they will have an actual return that is higher than the published return of the fund, i.e. the Dollar- Weighted Rate of Return will exceed the Time-Weighted Rate of Return. The findings indicate that investors are destroying value by actively timing their capital flows. The research also showed that a large percentage of the general investor community would have perceived larger returns by following a constant investment strategy.
MBA - WBS
Keywords: Unit trusts; Unit trusts returns